Slovenski zaporski sistem - razvoj in stanje po 25 letih - Hacin, Rok (Teorija in praksa, 2020)
The paper focuses on changes in the structure of the Slovenian prison population and prison workers, which partly reflect changes in the penal policy in the penitentiary field, especially the part concerning the institutional capacity of prisons. An analysis of prison statistics shows the intensification of sanctioning during the second half of the 1990s, as evidenced by increases in the prison population, imprisonment levels, and the number of persons under long-term prison sentences. In the period 1995-2018, most prisons faced overcrowding, leading to the recruitment of a bigger number of prison officers and the construction of new prisons and departments. The stagnating number of specialised workers responsible for the treatment of prisoners highlights the prioritisation of the security component over prisoner rehabilitation.
Keywords: imprisonment rate; kaznovalna politika; penal policy; prison population; prison staff; Slovenia; Slovenija; stopnja zapiranja; zaporska populacija; zaporski delavci